Birds of the Mongol Empire - Anderson, Eugene N. (Ethnobiology Letters, 2016)
The Mongol Empire, the largest contiguous empire the world has ever known, had, among other things, a goodly number of falconers, poultry raisers, birdcatchers, cooks, and other experts on various aspects of birding. We have records of this, largely in the Yinshan Zhengyao, the court nutrition manual of the Mongol empire in China (the Yuan Dynasty). It discusses in some detail 22 bird taxa, from swans to chickens. The Huihui Yaofang, a medical encyclopedia, lists ten taxa used medicinally. Marco Polo also made notes on Mongol bird use. There are a few other records. This allows us to draw conclusions about Mongol ornithology, which apparently was sophisticated and detailed.